3D hierarchically branched Cu2S/ZnO heterojunction nanowire arrays for enhanced solar water splitting. (March 2023) - Luo, Siyuan; Zhang, Shuai; Yuan, Hewei; Wu, Zhenhua; Li, Ming
Abstract: The construction of three-dimensional (3D) hierarchically heterostructured nanoarrays is proven to be an efficient approach to developing high-performance photoelectrochemical (PEC) cells for water splitting. Here, novel 3D hierarchically branched Cu2 S/ZnO heterojunction nanowire arrays (NWAs) are fabricated as photocathodes for enhanced PEC water splitting. The pristine Cu2 S NWAs are pre-grown on Cu substrates by a facile gas-solid reaction at room temperature, followed by ZnO nanospike branches decoration. The obtained 3D Cu2 S/ZnO NWAs demonstrate an improved light trapping ability of 93.7–99.0% in the wide wavelength range of 250–850 nm. Furthermore, the photocurrent density of 3D photocathodes is more than four times higher than that of the pristine Cu2 S NWAs, and it has an optimal incident photon to current efficiency (IPCE) of 10.5% at 450 nm. In addition, the mechanism of greatly enhanced PEC performance of the 3D heterostructures can be attributed to the increased light absorption and the stepwise band-edge structure for charge separation and transport. This strategy demonstrates an alternative route for the large-scale fabrication of high-performance PEC cells with low-cost nanostructured photocathodes. Graphical Abstract: 3D hierarchically branched Cu2 S/ZnO heterojunction nanowire arrays are designed and fabricated on Cu substrates as photocathodes for greatly enhanced photoelectrochemical water splitting. ga1